2022
DOI: 10.21203/rs.3.rs-1687264/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of Echocardiography in the Assessment of Cardiac Involvement in Takayasu Arteritis

Abstract: Background: The aim of this study is to investigate echocardiographic features of patients with cardiac involvement and evaluate the value of echocardiography in Takayasu arteritis (TA). Methods:All patients with TA admitted from January 2015 to December 2021 were classified into patients with cardiac involvement (group 1, n=68) and patients without cardiac involvement (group 2, n=59). This retrospective study compared the clinical manifestations and echocardiographic parameters between the two groups and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…The most frequent conditions were myocarditis, identified in six patients, and severe aortic regurgitation, observed in two cases. In line with our study, previous studies reported myocardial involvement in approximately 25 to 53% of TA patients in various studies [28,30,31]. It was suggested that myocardial involvement in TA patients might be associated with factors such as early age of disease onset, lack of classic risk factors, and more active disease [30].…”
Section: Discussionsupporting
confidence: 91%
“…The most frequent conditions were myocarditis, identified in six patients, and severe aortic regurgitation, observed in two cases. In line with our study, previous studies reported myocardial involvement in approximately 25 to 53% of TA patients in various studies [28,30,31]. It was suggested that myocardial involvement in TA patients might be associated with factors such as early age of disease onset, lack of classic risk factors, and more active disease [30].…”
Section: Discussionsupporting
confidence: 91%